State of the World's Indigenous Peoples - United Nations (United Nations, 2016)
This publication sets out to examine the major challenges for indigenous peoples to obtain adequate access to and utilization of quality health care services. It provides an important background to many of the health issues that indigenous peoples are currently facing. Improving indigenous peoples’ health remains a critical challenge for indigenous peoples, States and the United Nations. Indigenous peoples’ health status is severely affected by their living conditions, income levels, employment rates, access to safe water, sanitation, health services and food availability. They also face destruction to their lands, territories and resources, which are essential to their very survival. Other threats include climate change and environmental contamination. Geographical isolation and poverty results in not having the means to pay high cost for transport or treatment resulting in major structural barriers in accessing health care, further compounded by discrimination, racism and a lack of cultural understanding and sensitivity. Many health systems do not reflect the social and cultural practices and beliefs of indigenous peoples. At the same time, it is often difficult to obtain a global assessment of indigenous peoples’ health status because of the lack of data. More work is required in building existing data collection systems to include data on indigenous peoples and their communities.This study examines issues, progress and challenges in efforts to improve the safety and wellbeing of motorcycle riders through the use of approved motorcycle helmets. The growth in motorcycles is accompanied by an increase in serious and fatal accidents. Evidence shows that once internationally harmonized helmet regulations, such as the UN Regulation No. 22 type-approval system for helmets, are in place and laws on helmet wearing are enforced, these trends tend to reverse. In examining the relationship of income growth and national motorcycle fleet expansion, this study argues the socio-economic case for introduction of helmet regulations and their enforcement by delivering a benefit-cost analysis of taking such legislative actions.